2005
DOI: 10.1364/ao.44.004211
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of soot particle vaporization effects during laser-induced incandescence with time-resolved light scattering

Abstract: Although laser-induced incandescence (LII) has been successfully used for soot volume fraction and particle size measurements, uncertainties remain regarding issues of soot vaporization leading to mass loss and morphological changes occurring in soot due to intense heating. Prompt LII detection schemes are often based on the assumption that the associated time scale is shorter than the time scale of soot vaporization or sublimation. The validity of such assumptions is the focus of the current study. Time-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 36 publications
2
21
0
Order By: Relevance
“…114 The larger aggregates do not appear to be effective sites for heterogeneous cluster nucleation, e.g., the large regions of disordered carbon in Figure 6 are not apparent on the aggregate in Figure 5. At all fluences above the threshold for new particle formation, the median size of the large-mode aggregates is smaller than that of the non-irradiated particles, as shown in Our conclusions are consistent with those of Dasch, 34 Witze et al, 35 and Yoder et al 36 who measured changes in scattering and absorption cross sections during laser irradiation of soot and hypothesized that particle size reduction at fluences above 0.2 J/cm 2 occurred by vaporization of the particle. Our conclusions are also consistent with those of Vander Wal et al [29][30][31][32] who deduced from TEM images of laser-irradiated soot that aggregates do not disaggregate into primary particles upon laser irradiation but at high fluences lose mass via vaporization of primary particles.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…114 The larger aggregates do not appear to be effective sites for heterogeneous cluster nucleation, e.g., the large regions of disordered carbon in Figure 6 are not apparent on the aggregate in Figure 5. At all fluences above the threshold for new particle formation, the median size of the large-mode aggregates is smaller than that of the non-irradiated particles, as shown in Our conclusions are consistent with those of Dasch, 34 Witze et al, 35 and Yoder et al 36 who measured changes in scattering and absorption cross sections during laser irradiation of soot and hypothesized that particle size reduction at fluences above 0.2 J/cm 2 occurred by vaporization of the particle. Our conclusions are also consistent with those of Vander Wal et al [29][30][31][32] who deduced from TEM images of laser-irradiated soot that aggregates do not disaggregate into primary particles upon laser irradiation but at high fluences lose mass via vaporization of primary particles.…”
Section: Discussionsupporting
confidence: 93%
“…Witze et al 35 and Yoder et al 36 similarly measured changes in 532-nm 35 Previous studies demonstrated that carbon atoms are released from soot irradiated at 193 nm 38 and that C 2 is released by irradiation at 516, 563, and 193 nm. [38][39][40][41] Using an SMPS to measure size distributions, Stipe et al 42 observed nanoparticle production from soot aggregates exposed to 193-nm radiation.…”
Section: Previous Resultsmentioning
confidence: 99%
“…On the other hand, too high laser fluence can vaporize the soot to certain depth, leaving less material to incandesce. Although the LII was operated at low fluence levels »0.15 J/cm 2 , below the often used threshold for soot vaporization of 0.2 J/cm 2 , fluence should be below 0.1 J/cm 2 to eliminate the possibility of any soot vaporization (Yoder et al 2005). Therefore, this effect cannot be completely excluded.…”
Section: Effect Of Particle Morphology and Sizementioning
confidence: 99%
“…Recent results by Yoder et al [33] obtained using combined LII and Rayleigh scattering indicate that the mass loss in reality occurs much earlier. At a fluence of 0.61 J/cm 2 in their work, mass loss and laser heating was found to occur on the same time-scale.…”
Section: Spatially Resolved LII Signalsmentioning
confidence: 97%
“…At a fluence of 0.61 J/cm 2 in their work, mass loss and laser heating was found to occur on the same time-scale. Since particle temperatures could not have reached temperatures close to the sublimation temperature of soot at these early times, a non-thermal laser ablation process was suggested [33]. A possible physical process with these characteristics has been proposed by Michelsen [25].…”
Section: Spatially Resolved LII Signalsmentioning
confidence: 99%